Difitisme Arab: Awal Mula Kemunduran Arab Dan Dampaknya Terhadap Geobudaya Dan Geopolitik Dunia Arab - Us’an; Yoyo; Mastur; Suroto; Unaimah Sanaya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
What is really happening in the Arab world, despite the fact that this nation has achieved its glory for seven centuries? The problems facing the Arab nation are diverse, ranging from economic inequality to a crisis of cultural identity. Sykes-Picot In 1916, the Arab states, prone to internal conflict, were born. This agreement aimed to regulate their respective zones of influence in the Middle East and divide the Ottoman Empire. Britain also officially declared its support for the establishment of the State of Israel in the Palestinian territories. The birth of the State of Israel in 1948 marked a new chapter in the world political map, particularly in the Middle East. Therefore, deficientism led to the marginalization of the Islamic-Arab intellectual and cultural heritage. This research uses a literature review by taking several references from several journals, books, and various literature that support this research topic. The collected data was then interpreted to arrive at the research objectives. Based on the research results, it was found that deficientism had a direct impact on changes in the geopolitical constellation in the Arab region. In the geopolitical context, Arab countries were no longer active subjects in the international arena, but instead became objects of global interest. Furthermore, deficientism also impacted geoculture, where cultural values ​​experienced erosion due to the penetration of foreign cultures, global economic domination, and an identity crisis.